2011
DOI: 10.1038/ejcn.2011.176
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and K status influences bone mineral density and bone accrual in children and adolescents with celiac disease

Abstract: Background/Objectives: Children with celiac disease (CD) are at risk for decreased bone mineral density (BMD) because of fat-soluble vitamin malabsorption, inflammation and/or under-nutrition. The study objective was to determine the interrelationships between vitamin K/D status and lifestyle variables on BMD in children and adolescents with CD at diagnosis and after 1 year on the gluten-free diet (GFD). Subjects/Methods: Children and adolescents aged 3-17 years with biopsy proven CD at diagnosis and after 1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 39 publications
0
47
1
1
Order By: Relevance
“…Vitamin and mineral deficiencies may also be seen depending on malabsorption. The limited number of studies performed regarding the frequency of vitamin and mineral deficiencies in adult patients with celiac disease reported the frequency of vitamin and mineral deficiencies in varying rates up until now (11,14,17). A recent study Our particular study has revealed the presence of zinc deficiency in two-thirds of the patients with celiac disease at the time of diagnosis and vitamin D deficiency in more than half.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin and mineral deficiencies may also be seen depending on malabsorption. The limited number of studies performed regarding the frequency of vitamin and mineral deficiencies in adult patients with celiac disease reported the frequency of vitamin and mineral deficiencies in varying rates up until now (11,14,17). A recent study Our particular study has revealed the presence of zinc deficiency in two-thirds of the patients with celiac disease at the time of diagnosis and vitamin D deficiency in more than half.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with celiac disease experience metabolic bone diseases, including osteoporosis, osteopenia, and bone fractures (10,(17)(18)(19)(20)(21). There are several factors that affect the development of metabolic bone disease in patients with celiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…The small bowel damage from activated CD 8 + cells is characterized histologically by an invasion of lymphocytes into the epithelium and lamina propria, progression to crypt hyperplasia, and fi nally to blunting of intestinal villi (2) . Resolution of these intestinal lesions can occur after the removal of the inciting proteins from the susceptible individual ' s diet (8,9) . Untreated CD, however, is associated with malnutrition in 67 % of patients (10) .…”
Section: Introductionmentioning
confidence: 99%
“…In CD as well, low levels of vitamins A, E [47,49] and K [56] are found due to intestinal absorption impairment. Vitamin K is important for the hepatic synthesis both for coagulation factors (factors II, VII, IX, and X) and for coagulation inhibitors (protein C and protein S).…”
Section: Discussionmentioning
confidence: 99%